Tetes Tebu Menjadi Katalis Untuk Proses Pembuatan Biodiesel - Raysha Amelya; Indah Purnamasari; Muhammad Yerizam (Fakultas Teknik, 2023)
Sugar cane is a plant that is processed into crystal sugar because it contains high sugar content. Sugar production produces waste, one of which is molasses waste. This study aims to obtain molasses into a catalyst using the carbonization method and the sulfonation method. The sulfonation method uses variations in the concentration of 2, 4, 6, 8, and 10 N H2SO4 solution and variations in sulfonation time of 2, 4, and 6 hours to get the best molasses catalyst. Catalyst characterization includes surface acidity by acid-base titration, FT-IR, and SEM-EDX. This research also aims to produce biodiesel yield using the best molasses catalyst. The results of surface acidity analysis showed that the best molasses catalyst was obtained at 10 N H2SO4 concentration with 6 hours at 0.907 mmol/gr. FT-IR test results showed the presence of O=S=O functional groups at wave numbers 1149.74 cm-1 and 1038.57 cm-1. SEM and EDX analysis results showed that the molasses catalyst after sulfonation had smaller pores and more sulfur groups on the carbon sheet. The yield of biodiesel produced using a molasses catalyst was 84.51%.